1995
DOI: 10.1152/ajpregu.1995.269.3.r552
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pregnancy on activation of central pathways following atrial distension

Abstract: Stimulation of the atrial volume receptors increases neural traffic to the ventrolateral medulla, which in turn sends output to, and receives input from, the lateral hypothalamic area. An integrated reflex and hormonal response is thus initiated. We wished to investigate first whether atrial distension results in activation of selected nuclei in the forebrain and, second, whether pregnancy modifies this response. Rats were implanted with indwelling intracardiac balloons positioned at the superior vena caval/ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
34
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 0 publications
1
34
0
Order By: Relevance
“…Previous work has shown that activation of neurons in the hypothalamus in response to atrial receptor activation is reduced in pregnant rats compared with virgin rats (2). Thus the homeostatic mechanism that keeps fluid volume in check is suppressed during pregnancy.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Previous work has shown that activation of neurons in the hypothalamus in response to atrial receptor activation is reduced in pregnant rats compared with virgin rats (2). Thus the homeostatic mechanism that keeps fluid volume in check is suppressed during pregnancy.…”
Section: Discussionmentioning
confidence: 95%
“…We have shown that reflex control of renal function by the atrial volume receptors is attenuated during pregnancy such that the increase in sodium excretion and urine volume normally seen in response to atrial distension does not occur (8). In addition, there is a loss of activation of central components of the reflex pathway in response to atrial receptor stimulation in pregnant animals (2). These observations have led us to suggest that the homeostatic mechanisms that operate to maintain fluid balance are attenuated in the pregnant animal, thus allowing blood volume to increase.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Since then, arterial baroreflex impairment has been documented in several species studied in the conscious state, including dogs (23), rats (24,124), rabbits (21,97,162), goats (152), sheep (104,123), and humans (16,79,122,164,175,193). Reflex responses to atrial stretch are also blunted (51,94,95,103), which may contribute to retention of the expanded blood volume. The depressed baroreflex function observed during normal pregnancy appears to worsen in pregnancy-associated diseases such as preeclampsia (69,129,137,175,195).…”
mentioning
confidence: 99%
“…Thus lesions of the PVN attenuate the renal response to volume load (Lovick et al 1993;Haselton et al 1994). PVN parvocellular neurones exhibit early gene activation following plasma volume expansion (Narvaez et al 1993;Badoer et al 1997) or to stretch of the right atrium (Deng & Kaufman, 1995) and their activity is altered by stimulation of cardiac afferents (Lovick & Coote, 1988a,b, 1989. Activation of PVN neurones alters renal function via the renal nerves (Haselton & Vari, 1998).…”
mentioning
confidence: 99%